Smallpox Epidemic in Iquitos - López Vásquez, Jorge (1965)
In Iquitos , capital of Loreto , in the year 1963 and still evolving in 1964 , with expansion to other areas ; an outbreak of vesicular - pustular , rash illness with significant mortality rate was presented ; speculated considerably since the beginning of the nosographic entity if it was chickenpox , varicella or an overlap of both. The purpose of this paper is to clarify these differences , with epidemiological and clinical collected during the tenure of my internship in Hospital Health Center in this city Iquitos , to conclude that POX really tried to documentation. Present material patients from the general population of mosquitoes with which we realize the magnitude of the epidemic. And with a further patient Iquitos Hospital Health Center , who were treated in 1963 , the study will allow us a better view of the clinical picture of the disease. Is important therefore to know this reality, which caused great havoc and measures appropriate and timely could be controlled ; and when projected to the city of Lima in November and December 1963, with cases from Pucallpa and Iquitos.